Consumer negative opinions on stock returns: evidence from E-commerce reviews in China - Danni Wu; Zhenkun Zhou; Zhi Su (Financial Innovation)
Abstract This study investigates the significance of e-commerce consumer opinions regarding value in China’s A-share market. By analyzing a large dataset comprising over 18 million online consumer reviews on JD.com, we demonstrate that sentiments expressed in e-commerce reviews can influence stock returns. This indicates that consumer opinions on the e-commerce platform contain valuable information that can impact the stock market. Our findings show that Consumer Negative Sentiment Tendency (CNST) and One-Star Tendency (OST) have a negative effect on expected stock returns, even after controlling for firm characteristics such as market risk, illiquidity, idiosyncratic volatility, and asset growth. Further analysis indicates that CNST demonstrates stronger predictive power within the home appliance industry, under high sentiment conditions, in growth companies, and among firms with lower accounting transparency. We also find that CNST negatively predicts revenue surprises, earnings surprises, and cash flow shocks. These results suggest that consumer opinions and sentiments derived from e-commerce reviews highlight firms’ intrinsic worth and prospects. Future research could explore how firms, including suppliers and logistics companies, can leverage the information conveyed by consumer opinions on e-commerce platforms.